Outcomes Following Low-Profile Mesh Plate Osteosynthesis of Patella Fractures - Siljander, Matthew; Koueiter, Denise M.; Gandhi, Sapan; Wiater, Brett P.; Wiater, Patrick J. (The Journal of Knee Surgery, 2018)
Treatment of patella fractures is fraught with complications and historically poor functional outcomes. A fixation method that allows for early mobilization and decreases symptomatic hardware rates will improve knee range of motion, postoperative functional status, and reoperation rates. The purpose of this study was to evaluate the functional outcomes after locked plate osteosynthesis of patella fractures at a Level 1 trauma center. A retrospective case series was conducted of patients who underwent open reduction internal fixation (ORIF) of a patella fracture using a locked mesh plating technique coupled with neutralization of forces on the distal pole of the patella. Twelve patients were evaluated at a mean follow-up of 19 months (range, 6–30) with physical exam, functional outcomes, and radiographs. There were 9 women and 3 men with an average age of 66.1 years (range, 53–75). Radiographic bony union was achieved in all patients by 3-month follow-up. Visual Analog Pain Score averaged 1.7 (median, 1.0; range, 0–8), the mean Knee Outcome Score – Activities of Daily Living Scale was 83.9 (median, 92.1; range, 45.7–100.0), the mean Short Form Musculoskeletal Function Assessment (SMFA) Function Index was 9.9 (median, 3.7; range, 0.7–41.2), and the mean SMFA Bother Index was 11.1 (median, 3.1; range, 0–62.5). The SF-36 Physical Component Score mean was 48.4 ± 8.5 and the SF-36 Mental Component Score mean was 54.1 ± 9.6. No complications developed and there were no reoperations for nonunion, infection, or symptomatic hardware. This study demonstrates that locked plate osteosynthesis for operative patella fractures can reliably achieve bony union with potentially superior functional outcomes as compared with traditional methods. Further studies are needed to evaluate plate fixation for patella fractures, but early results are promising.
Keywords: patella fracture; mesh locking plate; osteosynthesis; low profile plate